"India’s Foreign Policy: Retrospect and Prospect” by Sumit Ganguly (ed.) (Meridiano 47 - Journal of Global Studies, 2017)
In this stimulating collection of scholarly essays, edited by Sumit Ganguly, the fifteen authors provide a balanced and insightful overview over India’s foreign policy. In Chapter 1, Ganguly argues that systemic (e.g., the Cold War), national (e.g., the experience of colonialism) and personal factors (e.g., Nehru) have contributed to the country’s foreign relations. It is this concept of three levels that structures the chapters in the book, helping the reader to navigate through often unwieldy and often unfamiliar issues.In Chapter 2, Basrur analyzes India-Pakistan relations, arguing that domestic politics pose the major obstacles to finding a lasting resolution. However, he strikes an optimistic tone arguing that through increased cooperation and communication, the Line of Control (LoC) could be “transcended”, and that we can expect cumulative improvement rather than a dramatic and unexpected peace deal. In Chapter 3 on India-Sri Lanka relations, Devotta shows that New Delhi’s concerns about security have outweighed Tamil Nadu’s particular preferences when dealing with the war-torn island to the South of India. The chapter is full of important details -e.g. mentioning China’s growing presence in Sri Lanka ”“ but t is unclear to the reader why this chapter is considerably longer and more detailed than the previous one, particularly since Pakistan plays a much more important role than Sri Lanka. In Chapter 4, Thakar sheds light on India-Bangladesh ties, arguing that despite no obvious obstacles relations are difficult mainly because of structural asymmetries and the suspicions that result from this unequal relationship. Recurring domestic instability on both sides further complicated matters. In Chapter 5, Garver elegantly summarizes the history of India-China relations in the context of shifting alliances during the Cold War, describing, among other aspects, the important role the Soviet Union played as one of India’s most reliable allies and a counterweight against the Pakistan- China alliance starting in the 1960s. Chapter 6 on India- Southeast Asia relations shows how difficult it has been in the past for India to exert influence in the region given its low economic integration due to its autarkic model. Despite these limitations, worries about Indian hegemony in the region have surfaced numerous times in the past decades.Chapter 7 (on India-Iran relations) is among the most interesting, reflecting how challenging it has been for India to maintain warm ties to an important energy supplier despite sharp criticism by India’s other allies, namely the United States, Israel and the Arab nations. Chapter 8 (on India-Israel relations) is a fascinating case study of how the Indian leadership used a brief window of opportunity after the Cold War to diversity its partnerships, making Israel into one of India’s most important providers of military equipment. Chapter 9 (on India-Korea ties) is more normative and points to commonalities regarding the dependence on Middle Eastern energy and the exposure to piracy in the Indian Ocean, but it remains somewhat unclear why Korea deserves a full chapter, while other important countries such as Turkey, Brazil, South Africa, Indonesia or the EU are left out. Chapter 10 (on India-Japan relations) is yet another example of how the Cold War constrained India’s foreign policy, given that Japan regarded the Soviet Union as a threat in the region. Despite not standing on the same side in the “cauldron of East-West confrontation”, the two managed to cooperate during the Cold War, and by the 1980s Japan was India’s largest aid donor. While both countries stand divided over India’s refusal to sign the NPT, the rise of China is likely to strengthen ties between India and Japan. Chapter 11 describes India’s ties to Russia, its former stalwart ally which remains India’s most important provider of arms, with over 70%, although this figure is set to decline, as Ollapally predicts. Despite their strongly differing trajectories (India is a rising democracy, Russia a declining autocracy), both share a range of common interests, such as combating radical Islam and containing China. Chapter 12 on India-US relations neatly shows how a unique combination of events including a severe balance of payment crisis in India allowed policy makers to overcome an anti-American establishment and lay the foundation of what is today one of the most important bilateral relationships in the world. Looking into the future, Kapur asks the important question of whether India’s continued problems with high levels of inequality, a lack of basic education and infrastructure hamper its ability to turn into America’s key ally in the region. A lot also depends on whether Afghanistan and Pakistan can turn into somewhat stable actors once US troops retreat in 2014.After looking at a series of bilateral relationships, the three final chapters deal with key themes, namely nuclear policy, economic policy and energy policy. Kirk rightly argues that India’s decision to go nuclear cannot be explained by China and Pakistan alone, for “other states in dangerous neighborhoods have forsworn the nuclear option”, adding that things need to be seen in the context of India’s search for recognition and respect in international affairs. Mukherji then explains why it took India so long to adopt market reforms that allowed India to overcome its notorious “Hindu growth rate.” Finally, Mistry shows how energy policy and foreign policy will be ever more interrelated as India will become increasingly dependent on imported energy. Here, it would have been interesting to hear the author’s views on the consequences of the nuclear accident in Japan on India’s long term energy planning.As Ganguly admits in the introduction, the book ostensibly lacks any mention of India’s growing ties to Latin America, particularly Brazil. Yet while Brazil- India ties are not yet comparable to India’s traditional bilateral relationships, future analyses of India’s foreign policy will need to take a more global approach, and include India’s views on other rising actors such as Brazil and Turkey ”“ after all, it is India’s growing outreach (reciprocated by the world’s growing interest in India) that has been the defining characteristic of India’s rise. Still, “India’s Foreign Policy: Retrospect and Prospect” is required reading not only for India scholars, but for anyone who seeks to develop a more profound understanding of Asian geopolitics.